Mn2 dimers encapsulated in silicon cages: a complex challenge to MC-SCF theory - Khanna, V; McGrady, JE (MDPI, 2022)
MC-SCF wavefunctions for three endohedral Mn/Si clusters, Mn2Si10, Mn2Si12, and [Mn2Si13]+, show evidence for strong static correlation, both in the Mn-Si bonds (‘in–out correlation’) and between the two Mn centers (‘up–down correlation’). We use both Restricted and Generalized Active Spaces (RAS and GAS) to place constraints on the configurations included in the trial wavefunction, showing that, particularly in the high-symmetry cases, the GAS approach captures more of the static correlation. The important correlating pairs are similar across the series, indicating that the electronic structure of the endohedral Mn2 unit is, to a first approximation, independent of the size of the silicon cage in which it is embedded.